Percutaneous balloon pulmonary valvuloplasty. - Tynan, M (1985)
Percutaneous pulmonary valvuloplasty was performed in 27 patients with congenital pulmonary valve stenosis. A fall in the transvalve gradient of at least 15 mm Hg occurred in 22 patients. In five there was little change in the severity of the stenosis; in three of these the pulmonary valve was dysplastic. None of the successfully treated patients had a dysplastic valve. The two other failures, early in the series, were probably due to inadequate balloon size. In one patient the procedure was performed twice, with a successful result from the second dilatation with a larger balloon. Follow up studies in a further six patients showed no evidence of restenosis in those who had been successfully treated and no late improvement in the remainder. There were no important complications. Percutaneous pulmonary valvuloplasty should be the initial treatment for congenital pulmonary valve stenosis, although when the valve is dysplastic the result is less likely to be satisfactory.